'Enforcing' national court judgments as arbitration awards under the New York convention. (26th September 2018) - Tan, David Isidore
Abstract: A main reason for the success of arbitration is the widespread enforceability of resulting awards under the New York Convention. In contrast, there is no comparable enforcement regime for national court judgments. The most recent attempt, the Hague Choice of Court Convention, has only been ratified by Mexico, the European Union, and Singapore. For this reason, many parties may choose arbitration over litigation to resolve their disputes, even if arbitration suffers from other difficulties (eg inability to join parties who have not consented to arbitration, or to hear non-arbitrable issues). But what if a national court judgment could be 'enforced' as an arbitration award? That is the unconventional challenge to conventional wisdom that this article seeks to address. To put it another way, this article explores the possibility of 'enforcing' national court judgments under the New York Convention. The word 'enforcing' is used loosely here, because the solutions explored do not involve the actual enforcement of national court judgments. Rather, these solutions seek to enforce arbitration awards that order the same relief a national court judgment would grant, resulting in an effect that is identical to the enforcement of a judgment by the selected national court.